Daniel Kahneman: Mental economy and the Nobel of economy - Garcia-Marques, Leonel (2004)
In October 2002, Daniel Kahneman was ingratiated by thr Royal Swedish Academy of Sciences with the Nobel prize of economy for his integration of insights that stemmed from psychological research on the economy field, especially in what concerns human judgment and decision making under uncertainty. In Aplril 2003, the “Encontros ao Fim da Tarde com a Psicologia” organized by the Associação Portuguesa de Psicologia (APP), in collaboration with Livraria Barata, a tribute was payed to Kahenman’s work, presenting, during two sessions, some of the greatest contributions of this author to the study of decision making and judgment under uncertainty, and discussing the consequences of these contributions to the contemporary thinking about the concept of rationality. The present paper summarises and discusses the mains ideas presented during these sessions. DOI: http://dx.doi.org/10.17575/rpsicol.v17i2.462